TRPV1 gain-of-function mutation impairs pain and itch sensations in mice. Issue 1 (March 2018) - Duo, Lina; Hu, Linghan; Tian, Naxi; Cheng, Gen; Wang, Huijun; Lin, Zhimiao; Wang, Yun; Yang, Yong
Transient receptor potential vanilloid 1 (TRPV1) is a non-selective cation channel, which can detect various noxious stimuli that cause pain, inflammation, hyperalgesia, and itch. TRPV1 knock-out mice show deficiency in nociception, but the in vivo effects of persistent activation of TRPV1 are not completely understood. Here, we generated TRPV1 knock-in mice with a G564S mutation. In the heterologous expression system, an electrophysiological study showed that the G564S mutation in mouse TRPV1 caused increased basal current and a leftward shift of voltage dependence. Intriguingly, using behavioral analysis, we found that knock-in mice showed a thermosensory defect, impaired inflammatory thermal pain, and capsaicin sensitivity. We also demonstrated an attenuated behavioral response to the pruritic agent histamine in the knock-in mice. Indeed, calcium imaging together with electrophysiology showed that the overactive mutant had decreased capsaicin sensitivity. Western blot analysis revealed that the G564S mutant reduced TRPV1 phosphorylation and cell membrane trafficking. Together, we have generated a mouse model with a gain-of-function mutation in Trpv1 gene and demonstrated that the pain and histamine-dependent itch sensations in these mice are impaired due to a decreased phosphorylation level and reduced membrane localization of TRPV1.